2017
DOI: 10.1111/tpj.13602
|View full text |Cite
|
Sign up to set email alerts
|

The DNA translocase RAD5A acts independently of the other main DNA repair pathways, and requires both its ATPase and RING domain for activity in Arabidopsis thaliana

Abstract: Multiple pathways exist to repair DNA damage induced by methylating and crosslinking agents in Arabidopsis thaliana. The SWI2/SNF2 translocase RAD5A, the functional homolog of budding yeast Rad5 that is required for the error-free branch of post-replicative repair, plays a surprisingly prominent role in the repair of both kinds of lesions in Arabidopsis. Here we show that both the ATPase domain and the ubiquitination function of the RING domain of the Arabidopsis protein are essential for the cellular response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 74 publications
0
20
0
1
Order By: Relevance
“…We previously demonstrated that the RecQ helicase AtRECQ4A acts independently of AtRAD5A in CL repair (Mannuss et al ., ). The ATPase AtRAD5A is involved both regulatorily and mechanistically in the DNA damage tolerance pathway and thereby enables the error‐free repair of blocked replication forks (Chen et al ., ; Mannuss et al ., ; Kobbe et al ., ; Klemm et al ., ). To elucidate the role of AtHRQ1 in relation to AtRAD5A, we generated the hrq1‐1 rad5A‐2 double mutant.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…We previously demonstrated that the RecQ helicase AtRECQ4A acts independently of AtRAD5A in CL repair (Mannuss et al ., ). The ATPase AtRAD5A is involved both regulatorily and mechanistically in the DNA damage tolerance pathway and thereby enables the error‐free repair of blocked replication forks (Chen et al ., ; Mannuss et al ., ; Kobbe et al ., ; Klemm et al ., ). To elucidate the role of AtHRQ1 in relation to AtRAD5A, we generated the hrq1‐1 rad5A‐2 double mutant.…”
Section: Resultsmentioning
confidence: 97%
“…AtRAD5A defines a pathway in the repair of DNA CLs separate from the helicase RECQ4A and the nuclease MUS81 (Mannuss et al ., ). Furthermore, we recently demonstrated that AtRAD5A acts independently of NER, single‐strand break repair, microhomology‐mediated end‐joining and the ATM‐mediated DNA damage response (Klemm et al ., ). Therefore, it was surprising to find a common involvement of AtHRQ1 and AtRAD5A in DNA CL repair.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In agreement with increased gene expression and activity, the genetic inhibition of AtPARPs in parp1 and parp2 mutant plants enhanced the sensitivity of plant growth to methyl methane sulfonate (MMS, a DNA alkylation agent that induces N-alkyl lesions and single strand breaks (SSB)) and to bleomycin [97,100,108,117]. Similarly, formation of true leaves was reduced in parp2 seedlings grown on bleomycin and mitomycin C (a DNA cross-linking agent) [92].…”
Section: Poly(adp-ribosyl)ation In Plantsmentioning
confidence: 99%